Potential use of Ginger (Zinger officinale Rose) Extracts as Biopesticide against Myzuspersicae Sulzer (Hemiptera, Aphididae) on Pepper Crops - Mdellel Lassaad; Mquiteb Abderrahman; Guerban Abdallah; Sudayri Bader Sulaiman; Selman Al-Ouda; Al-Aid Soltan (International Journal of Entomology, 2025)
Chemical insecticides have been the primary method used by farmers to control pests. However, their negative environmental impacts, harmful effects on beneficial insects and human health, and prohibition in organic farming systems have driven the search for natural alternatives with insecticidal properties. These alternatives provide a safer and more sustainable way to control insect pests. Medicinal plants and their constituents play an important role in pest management. For example, ginger (Zingiber officinale) extracts contain bioactive compounds with insecticidal activities. The objective of this work was to track the population of the green peach aphid (Myzuspersicae) on pepper crops in a greenhouse, identify the active ingredients in ginger extracts, and evaluate the insecticidal effects of three concentrations of ginger-derived aqueous and essential oil extracts against M. persicae on pepper plants under laboratory and greenhouse conditions. The results demonstrate that M. persicae grows rapidly on pepper crops under greenhouse conditions, reaching high densities on leaves. The ginger extract contains two active ingredients with insecticidal effects against this pest. The significant reduction in aphid (M. persicae) populations indicates that Z. officinale aqueous extract (150 mL/L) and essential oil (2 mL/L) have strong potential for the biological control of this pest under greenhouse conditions. Thus, the use of ginger plant extract emerges as a promising alternative for reducing M. persicae infestations on pepper plants.
Keywords: Pepper